Germanic Preterite-Present Verbs and their Morphological and Semantic Peculiarities - Botsman, Andriy; Dmytruk, Olga (Current issues of Ukrainian linguistics: theory and practice, 2019)
The purpose of this article is to give detailed description to all possible semantic and morphological features of Germanic preterite-present verbs. Some research has dealt with the problem of preterite-present present verbs; however, semantic and morphological functions of these verbs were studied only by singling out verb characteristics, peculiarities, potential possibilities in different Germanic languages without any alignment of the obtained results. There is little information available on preterite-present verbs within the west Germanic and North Germanic (Scandinavian) subgroups. Semantic aspect of these verbs was analysed by some scholars, but it is still unknown how these verbs were formed in other Indo-European languages (Baltic, Slavonic, Romantic). The contradicting point of the available research is how those verbs are reflected in Latin and Greek. In spite of the fact that preterite-present verbs were studied in detail in terms of phonological characteristics, their morphological and semantic peculiarities were not taken into account and compared. Special attention should be given to the functioning and correlation of phonological and morphological peculiarities of those verbs. This paper offers the results of a detailed and consistent analysis of phonological and morphological peculiarities of preterite-present verbs. The paper aims at determining the morphological characteristics of preterite-present verbs, which were formed under the influence of phonological processes. The purpose of this study was to investigate the connection of Germanic preterite-present verbs with possible sources in other Indo-European languages. The authors define a set of characteristics peculiar of preterite-present verbs semantics. The functions of these verbs are analysed in detail. The authors attempt to analyse the nature of these verbs. The attention is paid to the functions of preterite- present verbs not only in the Germanic languages, but in other Indo-European languages, too. The comparative historical method is used here as the main one. The authors see this valid way of investigation as reliable and appropriate for the preterite-present verb analysis.
Keywords: consonant shift, preterite-present verbs, verb derivative semantics, verb semantics, vowel gradation.